Vulnerability and adaptation in flood-prone ecosystems of Bangladesh: a case study of rice farming households - Mohammad Chhiddikur Rahman; Md Abdur Rouf Sarkar; Md. Jahangir Kabir; Md. Shajedur Rahaman; Jatish C. Biswas; Md. Abdullah Aziz; Mohammad Ariful Islam; Md. Abdullah Al Mamun; Niaz Md. Farhat Rahman; Andrew M. McKenzie (Discover Sustainability)
Abstract Floods in Bangladesh significantly impact rice production, a vital element of food security. While regional flood effects have been extensively studied, the specific impacts on rice, the country’s primary staple, remain underexplored. This study assesses the effects of floods on rice production, availability, and prices, alongside identifying household vulnerabilities and adaptation strategies. Using both quantitative and qualitative data from secondary sources and interviews with farmers, we analyzed how floods affect rice cultivation and market dynamics. Our findings showed that floods predominantly affect wet season Aman rice, temporarily disrupting cultivation, national yield, and market prices. However, the adoption of stress-resistant varieties and improved agricultural practices has mitigated these effects. While floods have minimal effects on overall rice production, their consequences significantly increase rice prices at the retail level. Importantly, whereas floods prior to 2007 often resulted in substantial rice shortages, the post-2007 era, despite frequent and severe flooding, has witnessed a surplus in rice production. We estimated that despite five flood events in 2020, the country maintained a surplus of 2.9 million tons with minimal reliance on imports. This resilience is attributed to strategic planning, including the diversification of food sources and stockpiling. The government has strengthened the public food distribution system to address immediate food vulnerabilities and encouraged private imports to ensure a stable supply and market prices. Furthermore, government procurement policies are geared towards guaranteeing fair prices for rice farmers. Our findings underscore the importance of integrating these insights into policy frameworks to enhance flood adaptation strategies in Bangladesh.